Efficacy Study of Bulksource of Crude Cassava Water Extract as A Post Emergence Herbicide in Cowpea (Vigna Unguiculata (L) Walp) Production (2013)
Weed interference remains a major cause of low productivity of cowpea oral concern over synthetic herbicides has led to an increased interest in natural crop protection, in Order to achieve more environmentally safe methods of reducing weed pests damage in cowpea production in Nigeria. Two field trials were conducted in 2006and2007at Ijako -Owode in Ogun State, Nigeria The treatments were Bulk crude cassava water extract (CCWE from different cassava varieties) at the rates of 25 and 50% parquet at 0.50 and 1.00kg ai/ha and two controls: handweeded and unweeded The experiments were laid out in a randomized complete block, design (RCBD) with three replications. Data collected were analyzed and significant means were separated using analysis of variance (ANOVA) and Duncan multiple range test (DMRT) at p< 0.05. At commencement of the trial, the relative abundance of weed species was 81% broadleafed and 19% grasses. Results showed that Bulk CCWE at 50% showed significant difference (p<0.05) from paraquat at 1.00kgai/ha on phytotaxicity effects, while weed biomass and density recorded no significant difference (p>0.05). Higher leaf area (LA) vice recorded from Bulk CCWE with a significant difference (P<0. 05) from LA paraquat. However, all the yield component: number of pods, pod weight, seeds/pod and grain yield of Bulk CCWE were significantly higher (p<0.05) front paraquat treatments and comparable to handweeded while the least were obtained with unweeded Attributes of Bulk CCWE as a post- emergence herbicide candidate are discussed